2017
DOI: 10.1016/j.fct.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol as MDR reversion molecule in breast cancer: An overview

Abstract: Breast cancer is the most common cause of cancer mortality among women worldwide; therefore, a strategy to defeat breast cancer is an extremely important medical issue. One of the major challenges in this regard is multidrug resistance (MDR). Resveratrol, a well-known phytoestrogen, may be helpful as part of an overall strategy to defeat breast cancer. The mixed agonist and antagonist role of resveratrol for the estrogen receptor makes it a controversial but interesting molecule in cancer therapy, especially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 97 publications
(69 reference statements)
3
40
0
1
Order By: Relevance
“…Binding of integrin to ECM resulted in phosphorylation of FAK at several tyrosine residues including Tyr397 to increase kinase activities and promote the interaction of FAK with other proteins including SRC (30)(31)(32). One study found that FAK directly bond to cortactin (an actin regulator), which was not only a key force movement and focal adhesion conversion, but also affected cell survival (33). This study found 35 molecules (DEGs; proteins) distributed in this pathway (Supplemental Table 9), which suggested that the biological behavior of NFPA should be similar to that of other tumors, and that there should be a huge difference in cell adhesion between NFPAs and normal pituitaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of integrin to ECM resulted in phosphorylation of FAK at several tyrosine residues including Tyr397 to increase kinase activities and promote the interaction of FAK with other proteins including SRC (30)(31)(32). One study found that FAK directly bond to cortactin (an actin regulator), which was not only a key force movement and focal adhesion conversion, but also affected cell survival (33). This study found 35 molecules (DEGs; proteins) distributed in this pathway (Supplemental Table 9), which suggested that the biological behavior of NFPA should be similar to that of other tumors, and that there should be a huge difference in cell adhesion between NFPAs and normal pituitaries.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cGMP promoted tumorigenesis and anticancer effects. For example, the activated cGMP/PKG pathway induced multiple cancers (33,(35)(36)(37). Studies found specifically activated protein kinase G1 (PKG1) triggered MAPK signaling pathway to promote growth of melanoma (38).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ABC transporter‐mediated multidrug resistance is one of the main obstacles for the successful treatment of cancer, because of their ability to pump drugs out of the cells . Drug delivery on the basis of nanoparticles, including gold, silver, quantum dots (QDs), titanium dioxide, carbon‐based nanomaterial, is a promising tool to overcome the drug resistance caused by ABC transporters.…”
Section: Introductionmentioning
confidence: 99%
“…Leukemia patients whose tumor cells are MDR could benefit from treatment using various MDR inhibitors, ranging from conventional ones such as: verapamil to less toxic ones . For instance, the recent use of dual‐drug delivery systems based on nanoparticles and chemotherapeutic agents can interfere with the P‐gp drug pumps and lead to enhancement of drug accumulation in the leukemic cells . Several trials show encouraging results in using cyclosporine A (CsA) in the treatment of AML patients , but perhaps the most prominent application for using MDR inhibitors was provided by Chan et al., in which a high cure rate (91%) was achieved by using CsA in combination with chemotherapy .…”
Section: Introductionmentioning
confidence: 99%